Echocardiographic findings in patients with chronic obstructive pulmonary disease - Patil, Sarang; Patil, Suresh (International Journal of Research in Medical Sciences, 2019)
Background: Chronic obstructive pulmonary disease (COPD) is a common respiratory condition involving the airways and characterized by airflow limitation. Pulmonary hypertension (PH) is a well-known predictor of increased morbidity and mortality in COPD. The present study was done to assess the cardiac changes in patients diagnosed with COPD in this department using two-dimensional echocardiography. Methods: This observational study was conducted on fifty patients admitted with signs and symptoms suggestive of COPD in the Department of Pulmonary Medicine, Dr. DY Patil Medical College, Navi Mumbai from January 2018 to December 2018. Pulmonary function tests (PFT) were done in all and patients were graded according to the severity of COPD with guidelines given by Global initiative for Obstructive Lung Disease (GOLD). Comprehensive two-dimensional echocardiography was performed. Results: The most common age group was 60 to 69 years. There were 68% males and 32% females. Mean body mass index of the patients included in the study was 27.8±8.13 kg/m2. COPD according to the GOLD classification was mild, moderate, severe and very severe in 12%, 36%, 30% and 22% of the patients. PH was diagnosed in 56% of the patients, Cor pulmonale in 54%, right ventricular dilatation in 48%, right atrial dilatation in 38%, inter-ventricular septal wall motion abnormality in 18% and right ventricular failure in 14% of the patients. Conclusions: Echocardiography examination is a reliable method in COPD patient to assess PH and helps in early detection of cardiac complications in COPD cases giving time for early interventions.